2006
DOI: 10.1097/01.hjh.0000198028.84353.86
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, awareness, treatment, and control of hypertension in the elderly: the Three City study

Abstract: Management of hypertension, and particularly its control among treated hypertensive patients, needs to be improved in people aged 65 years and over.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
50
4
5

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 90 publications
(69 citation statements)
references
References 18 publications
10
50
4
5
Order By: Relevance
“…36 The prevalence of hypertension and its awareness, treatment and control in studies conducted exclusively among the elderly and using our criteria for defining hypertension is given in Table 5. 14,15,17,[19][20][21][22][23][24][25][26][27] Although most of these studies reported a lower prevalence of hypertension 17,20,[22][23][24][25]27 than what we observed (73.9%), some Hypertension among elderly Singaporeans R Malhotra et al reported a similar prevalence 14,19,21,23,26 or, in one study, 15 an even higher prevalence. Other than differences in the BP measurement instrument (manual or electronic) and number of readings (two or three) used for defining SBP and DBP, the variation could also reflect differences in demographic (for example, age, gender, ethnicity) and lifestyle (for example, diet, physical activity) profiles and in economic development across countries (prevalence is usually higher in more developed economies 38 ).…”
Section: Discussioncontrasting
confidence: 47%
See 4 more Smart Citations
“…36 The prevalence of hypertension and its awareness, treatment and control in studies conducted exclusively among the elderly and using our criteria for defining hypertension is given in Table 5. 14,15,17,[19][20][21][22][23][24][25][26][27] Although most of these studies reported a lower prevalence of hypertension 17,20,[22][23][24][25]27 than what we observed (73.9%), some Hypertension among elderly Singaporeans R Malhotra et al reported a similar prevalence 14,19,21,23,26 or, in one study, 15 an even higher prevalence. Other than differences in the BP measurement instrument (manual or electronic) and number of readings (two or three) used for defining SBP and DBP, the variation could also reflect differences in demographic (for example, age, gender, ethnicity) and lifestyle (for example, diet, physical activity) profiles and in economic development across countries (prevalence is usually higher in more developed economies 38 ).…”
Section: Discussioncontrasting
confidence: 47%
“…Many previous population-based surveys also report findings based on BP values measured during a single visit. 6,[15][16][17][19][20][21][22]24,27 Given the survey's cross-sectional design, the identified correlates of hypertension are not necessarily causal risk factors. However, most of the sociodemographic variables we consider must have preceded the development of hypertension.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations